2020
DOI: 10.1007/s13178-020-00491-5
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood Intentions, Pathways to Parenthood, and Experiences in the Health Services of Trans People: an Exploratory Study in Portugal

Abstract: Background It has been speculated for several years that trans identity and parenthood could be incompatible. However, studies investigating the parental intentions of trans individuals stress that they have motivations and parental intentions similar to cis people. Fertility preservation is a way for trans people to achieve parenthood; still, information about these procedures is not always provided, and implications on trans people well-being are not always discussed with health professionals. Methods In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…The participants' younger age was clearer among those without children and especially among those intending to have them, which is consistent with previous studies (e.g., Auer et al 2018;Charter et al 2018;Marinho et al 2021). Another result that aligned with previous studies (Carrara et al 2019;Giami and Beaubatie 2014) is the relatively high level of educational attainment in the population, and this higher educational level was especially evident among participants with children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The participants' younger age was clearer among those without children and especially among those intending to have them, which is consistent with previous studies (e.g., Auer et al 2018;Charter et al 2018;Marinho et al 2021). Another result that aligned with previous studies (Carrara et al 2019;Giami and Beaubatie 2014) is the relatively high level of educational attainment in the population, and this higher educational level was especially evident among participants with children.…”
Section: Discussionsupporting
confidence: 90%
“…While most papers focused on distress and treatment aspects, the perspective of well-being and development was present in a couple of studies in the thematic category of gender trajectories and identities. These included qualitative studies on the experiences of trans youth (Hilario and Marques 2020), gender diversity in infancy and in the school context (Saleiro 2017), trajectories of recognition and coming to terms with gender identity/ies (Pinto and Moleiro 2015), and the parenthood intentions of trans and non-binary people (Marinho et al 2021). The latter work is in line with a critical turn in discussing sex and gender, as well as in relationship diversity; this is consistent with the paradigm of queer relationship diversity and intimacies proposed by Hammack et al (2019), and relational citizenship by Santos (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Their motivations included some that are similar to those revealed in previous studies of heterosexual individuals (e.g., Langdridge et al, 2015), such as the personal and psychological rewards of parenting, and the belief that becoming a parent is a key developmental stage in life. Similarly, a study of transexual individuals in Portugal found that the key reason to become a parent was the personal fulfillment that parenthood would bring them and the potential to ensure family continuity (Marinho, Gato, & Coimbra, 2020). Other reasons uncovered by Goldberg et al (2012) seemed to be shaped more by individuals’ status as sexual minorities such as teaching a child to be tolerant so that society could become more accepting.…”
Section: The Mediating Effects Of Social Self-concept On Gender Sexua...mentioning
confidence: 99%
“…For example, Petit, Julien, and Chamberland (2018) found that Canadian pre-and post-transition trans parents struggled in different ways at different times in their lives: those who had children prior to gender transition struggled to have their gender identity accepted and supported by family members, while those who had children post-transition often faced considerable challenges with institutional services that presumed cisgender parenthood. Although some transgender and non-binary adults do not want to have children, studies also have indicated that many transgender and non-binary young adults do want to become parents (e.g., Marinho, Gato, & Coimbra, 2020;. Looking at the parenthood plans of transgender and non-binary people in the UK, Tasker and Gato (2020) found that gender identity trajectories had implications for future parenthood; likewise future parenthood had complex implications for the recognition of gender identity.…”
Section: The Fourth Research Wave: Family and Self-definition In Contemporary Diversitymentioning
confidence: 99%
“…In the UK gender identity clinics had begun to take on board the need to discuss options concerning fertility preservation when discussing hormonal and surgical interventions but assisted reproduction clinics and funding were oriented around cisgender clientele. In Portugal, Marinho et al (2020) considered the parenthood intentions of Portuguese transgender and non-binary people and their experiences with health services.…”
Section: The Fourth Research Wave: Family and Self-definition In Contemporary Diversitymentioning
confidence: 99%